Optimizing cold storage for Orius laevigatus: the role of genetic selection and fluctuating thermal regimes in enhancing survival and fecundity - Amador Rodríguez-Gómez; Adrián Sapiña-Solano; María del Carmen Reche; Virginia Balanza; Ana Belén Abelaira; Pablo Bielza (Journal of Pest Science, 2025)
The optimization of cold storage for biological control agents, such as Orius laevigatus , is critical for addressing mismatches in supply and demand in mass-rearing systems. This study evaluates the survival and reproductive quality of O. laevigatus under various storage conditions, including constant low temperatures (CLTs) and fluctuating thermal regimes (FTRs), with and without food. Additionally, it explores the impact of genetic selection for improved traits on storage tolerance. Selected strains (2POL) adapted to suboptimal diets exhibited significantly higher survival during starvation and storage compared to commercial and wild populations. At 10 °C, improved strains displayed enhanced survival, particularly during prolonged storage periods, and maintained higher post-storage fecundity. Comparisons between temperature regimes revealed that FTRs (e.g., 12–8 °C and 15–6 °C) resulted in higher survival and fecundity after storage than CLTs. The presence of food during storage was found to be crucial for maximizing survival and quality, especially under prolonged storage conditions. These results demonstrate the potential of genetic improvement to enhance the viability and effectiveness of biological control agents under cold storage. Furthermore, FTR protocols offer a promising strategy to balance cold stress with metabolic needs, improving long-term storage outcomes. Further refinement of temperature regimes and feeding strategies could enhance the practical application of FTRs in industrial rearing systems, ensuring efficient and high-quality biological control agent supply.